IMPROVING STUDENTS' ENGLISH-SPEAKING MOTIVATION AND ACHIEVEMENT THROUGH FIELD TRIP VIDEOS - Irawati, Yuyun (ENGLISH JOURNAL, 2023)
An essential component of a student's learning process is motivation. The primary issue, specifically VII A in SMP Khadijah 2 Surabaya academic year 2022/2023, was identified by the researcher as a lack of desire during speaking class. The pupils were apathetic, easily bored, did not participate in the learning process, and did not give the assignment their full attention. The purpose of the study is to implement the use of field trip videos to increase the students' English speaking motivation and achievement in VIIA students of SMP Khadijah 2 Surabaya so the lack of motivation and achievement can be solved. The research question for this study is how can the use of field trips videos motivate students to speak English? And, how can the use of field trips videos improve students 'English speaking achievement? To address the issue of low motivation and achievement, the researcher employed classroom action research to install field trip videos. To assess the researcher's data, qualitative and quantitative methodologies are both used. The qualitative approach is used to gather data utilizing field notes, surveys, observations, and interviews. For each cycle, data from the speaking pre- and post-tests are gathered using the quantitative method. The findings show that field trip videos improves students' English speaking motivation and achievement in speaking class. This can be seen from the improvement in each cycle. Nineteen of the twenty-four students received score that exceeded the Minimum Mastery Requirement (KKM).